2005
DOI: 10.1136/hrt.2005.063230
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced vagal modulation and exercise induced ischaemia of the inferoposterior myocardium

Abstract: Objective: To determine whether the Bezold-Jarisch reflex or enhancement of vagal nerves, which are preferentially distributed in the inferoposterior myocardium, results from exercise induced ischaemia in this region. Methods: On the basis of exercise myocardial scintigraphy and coronary angiography, 145 patients were classified as follows: group I, 34 patients with inferoposterior ischaemia; group A, 32 with anterior ischaemia; and control, 79 without ischaemia. The relation between ischaemic areas and ECG le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
1
22
0
1
Order By: Relevance
“…However, reversible regional perfusion abnormality involving inferoposterior wall was associated with vagal enhancement despite disproportional sample size of our patients. A similar cardioinhibitory response or Bezold-Jarisch reflex has been observed in the myocardial infarction and/or ischemia involving the inferoposterior wall [10,14], in which vagal nerve distribution is also predominant [26][27][28][29]. In the present results, however, the contribution of BezoldJarisch reflex to abnormal blood pressure response is not considered large compared to that in our previous report [10]; only 1/3 patients with reversible regional perfusion abnormality in inferoposterior wall showed abnormal blood pressure response and 4/5 patients with abnormal blood pressure response did not show regional perfusion abnormality in inferoposterior wall in the present HCM patients.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…However, reversible regional perfusion abnormality involving inferoposterior wall was associated with vagal enhancement despite disproportional sample size of our patients. A similar cardioinhibitory response or Bezold-Jarisch reflex has been observed in the myocardial infarction and/or ischemia involving the inferoposterior wall [10,14], in which vagal nerve distribution is also predominant [26][27][28][29]. In the present results, however, the contribution of BezoldJarisch reflex to abnormal blood pressure response is not considered large compared to that in our previous report [10]; only 1/3 patients with reversible regional perfusion abnormality in inferoposterior wall showed abnormal blood pressure response and 4/5 patients with abnormal blood pressure response did not show regional perfusion abnormality in inferoposterior wall in the present HCM patients.…”
Section: Discussionsupporting
confidence: 70%
“…Beat-to-beat heart rate data during exercise testing were sampled at a frequency of 500 Hz using personal computer and software (MemCalc/Tarawa, GMS, Tokyo, Japan) as previous described [10]. High frequency component (HF, 0.15-0.40 Hz) was used in the estimation of vagal modulation from short-duration recordings [19][20][21]; HF was extracted every minute and averaged for 5 min immediately before exercise and immediately after a cool-down period following exercise.…”
Section: Vagal Modulationmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is known as Bezold-Jarisch reflex, which has been explained by the preferential distribution of cardiac receptors along afferent vagal pathways in the inferior wall of the left ventricle [4]. We previously reported that the vagal modulation as assessed by HF and CCV HF was enhanced through exercise-induced myocardial ischemia of the inferoposterior myocardium [5]. Thus, in the present case, the combination of vagal enhancement provoked by exercise-induced inferior ischemia and sustainment of sympathetic activation after exercise possibly led to audibly perceptible heart rate fluctuation without bradycardia or hypotension.…”
Section: Discussionmentioning
confidence: 99%